2020
DOI: 10.1016/j.celrep.2020.107661
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Regulation of Developmental Time in the Kidney

Abstract: Highlights d Circadian clock oscillations emerge in mouse fetal kidneys prior to birth d Onset of fetal rhythms is timed to a transition in branching rate d Absence of Bmal1, a core clock gene, results in developmental defects d The clock functions as a developmental timer that regulates organogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…It is well-known that tubulointerstitial fibrosis, characterized by excessive extracellular matrix (ECM) deposition, inflammation, and remodeling, is the hallmark of a wide variety of progressive chronic kidney diseases. 18 Here, by generating a mouse line with induced deletion of Bmal1 in adulthood (iKO) to bypass the possible developmental defects in conventional knockouts, 7,19 we confirmed that Bmal1 mediates a major portion of the diurnal variation of urinary volume, and sodium and potassium excretion. Furthermore, we explored the effect of Bmal1 deficiency on renal fibrosis and the underlying mechanisms using a mouse model of unilateral ureteral obstruction (UUO).…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…It is well-known that tubulointerstitial fibrosis, characterized by excessive extracellular matrix (ECM) deposition, inflammation, and remodeling, is the hallmark of a wide variety of progressive chronic kidney diseases. 18 Here, by generating a mouse line with induced deletion of Bmal1 in adulthood (iKO) to bypass the possible developmental defects in conventional knockouts, 7,19 we confirmed that Bmal1 mediates a major portion of the diurnal variation of urinary volume, and sodium and potassium excretion. Furthermore, we explored the effect of Bmal1 deficiency on renal fibrosis and the underlying mechanisms using a mouse model of unilateral ureteral obstruction (UUO).…”
Section: Introductionmentioning
confidence: 71%
“…Besides, the current study used mice whose Bmal1 was depleted only during adult‐life, while in the previous study, Clock was prenatally knocked out 25 . Indeed, Dan et al most recently supported that an intact fetal clock is indispensable to proper kidney development and normal kidney function establishment in adults 19 . Thus, potentially adverse effects during embryonic development of Clock gene depletion may also contribute to its unfavorable phenotypes on renal fibrosis.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations